Hormone Receptor Positive/HER2 Negative Breast Cancer With Isolated Bladder Metastasis: A Rare Case - Noman Ahmed Jang Khan MD; Mahmoud Abdallah MD; Maria Tria Tirona MD, FACP (SAGE Publishing, 2021)
Breast cancer is the most common cancer diagnosed in women in North America. Hormone receptor positive (HR+) and HER2 negative (HER2−) breast cancers account for at least 60% to 70% of all breast cancer cases. They usually metastasize to lymph nodes, bones, liver, lungs, and brain. Urinary bladder is a very unusual site for metastatic HR+/HER2− breast cancer and occurs in only 2% of all metastatic disease. In this article, we present a case of a 63-year-old female with locally advanced breast cancer who underwent mastectomy, adjuvant chemotherapy, radiation, and hormonal therapy. She was in remission for almost 17 years and subsequently presented with hematuria and lower abdominal pain. Cystoscopy was performed, which showed evidence of bladder wall thickening. Histopathology showed metastatic HR+/HER2− breast cancer consistent with her history of breast primary. Imaging studies did not show any other evidence of metastatic disease. She was started on cyclin D kinase 4/6 inhibitor, palbociclib, in combination with an aromatase inhibitor, letrozole. This is an exceedingly rare case of HR+ and HER2− breast cancer with metastasis to the urinary bladder. The late onset of recurrence with bladder metastasis makes this case very unique and to our knowledge only few similar cases have been reported in the literature.